THE USE OF E-MODULE-BASED ENGLISH LEARNING ON SIYASAH SYAR'IYAH STUDENTS STAIN BENGKALIS - Rini Fitria; Ahmad Jailani; Nurjayanti Nurjayanti (INOVISH JOURNAL, 2022)
English is one of the subjects that must be studied by students. In transferring competence, a special method is needed, especially for students who are not from the English Department. This research was conducted to measure the students' ability from the learning outcomes of e-module-based English courses. This research method can be categorized as quantitative research. The Mann-Whiteney test was chosen as an alternative in data processing. The total population in this study was 57 students of semester 1 of the Siyasah Syar'iyah Study Program class A and class B for one semester. The result is that the students' ability to use the English module between classes A and B is on average the same. This means that students do not find difficulties in using English e-modules.